ANALISIS FRAMING PENEGAKAN HUKUM ANGKUTAN PADA MEDIA ONLINE DETIKSULTRA.COM - Mahdar; Maudhy Satyadharma; Sayyid Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The research was conducted to analyze the news framing of Supervision and Law Enforcement on Detiksultra.com Online Media from November-December 2022. The research used Entman's framing analysis with four things, namely Define Problems, Diagnose Cause, Make Moral Judgment and Treatment Recommendation. The conclusion of this study is that DetikSultra.com Online Media frames the supervision and law enforcement activities of Road Transportation carried out by the Southeast Sulawesi Province Transportation Service because of the many violations committed so that it is hoped that safe, comfortable, humane transportation will occur and refers to applicable regulations.